Using community‐led development to build health communication about rheumatic heart disease in Aboriginal children: a developmental evaluation. (10th May 2021) - Mitchell, Alice G.; Diddo, Joseph; James, Alistair Djalolba; Guraylayla, Laurie; Jinmarabynana, Cindy; Carter, Abigail; Rankin, Stanley Djalarra; Djorlom, Gideon; Coleman, Carolyn; Scholes, Mason; Haynes, Emma; Remenyi, Boglarka; et al.
Abstract: Objective : A high prevalence of acute rheumatic fever (ARF) and rheumatic heart disease (RHD) among Aboriginal children in northern Australia is coupled with low understanding among families. This has negative impacts on children's health, limits opportunities for prevention and suggests that better health communication is needed. Methods : During an RHD echocardiography screening project, Aboriginal teachers in a remote community school created lessons to teach children about RHD in their home languages, drawing on principles of community‐led development. Access to community‐level RHD data, previously unknown to teachers and families, was a catalyst for this innovative work. Careful, iterative discussions among speakers of four Aboriginal languages ensured a culturally coherent narrative and accompanying teaching resources. Results : The evaluation demonstrated the importance of collective work, local Indigenous Knowledge and metaphors. As a result of the lessons, some children showed new responses and attitudes to skin infections and their RHD treatment. Language teachers used natural social networks to disseminate new information. A community interagency collaboration working to prevent RHD commenced. Conclusions and implications for public health : Action to address high rates of RHD must include effective health communication strategies that value Indigenous Knowledge, language and culture, collaborative leadership and respect for Indigenous data sovereignty.